HAPLOANDESITIC MELTS AT MAGMATIC TEMPERATURES: IN SITU, HIGH-TEMPERATURE STRUCTURE AND PROPERTIES OF MELTS ALONG THE JOIN K2SI4O9-K2 (KAI)4O9 TO 1236OC AT ATMOSPHERIC PRESSURE - Mysen B. (My University, 1996)
The structure of haploandesitic magma was modeled via in situ, high-temperature Raman spectroscopy along the join K2Si4O9-K2(KAl)4O9 from 25 to 1236°C. These glasses and melts consist of Q^4, Q^3, and Q^2 structural units. Aluminum substitutes for Si in all units. The disproportion reaction, 2Q^3 \tB Q^4 + Q^2, shifts to the right with increasing temperature (above the glass transition temperature) and with increasing Al/(Al + Si). Stepwise linear regression yields the temperature- and Al/(Al + Si)- dependence for the equilibrium constant for the disproportionation reaction,ln K = -2.7 +/- 0.1 - 1172 +/- 153T(K) + 12.6 +/- 0.9.AlAl + Si + 14.3 +/- 3.(AlAl + Si)2.The enthalpy of the reaction decrease with increasing Al/(Al + Si) from #11 kJ/mol at Al//(Al + Si) = 0 to about 3 kJ/mol at Al/(Al + Si) # 0.1 before increasing with further Al3+ \tB Si4+ substitution.